Relationship between Patient Knowledge and Attitude Level in the Use of Antibiotic at Tanjung Paku Community Health Center Solok City: Hubungan Tingkat Pengetahuan dan Sikap Pasien dalam Penggunaan Antibiotik di Puskesmas Tanjung Paku Kota Solok - Armal, Khairil; Azkia, Nisa; Afriani, Tika (Indonesian Journal of Pharmaceutical and Clinical Research, 2023)
Low levels of knowledge about the proper use of antibiotics can lead to incorrect usage, which raises the possibility of antibiotic side effects. The goal of this study is to evaluate patient attitudes and knowledge regarding the use of antibiotics at the community health center in Tanjung Paku Solok City. A questionnaire acted as the data collection tool in a cross-sectional study with a descriptive approach and accidental sampling as the sample process. 60 patients who met the inclusion criteria were included in the sample. The Chi Square test, partial T test, simultaneous F test, and multiple linear regression test were used to examine the results. The results revealed that in good category for knowledge is 57 people (95%), in enough category is 3 people (5%), and there is no one in less category. While the results for good category in attitude is 48 people (80%), in enough category is 12 people (20%) and there is no one in less category. It can be stated that the patients of community health center in Tanjung Paku Solok City has knowledge and attitude category in the use of antibiotic is good. The results of the analysis between knowledge and attitude is having a significant relationship (Sig. = 0.039) but has less influence value, and there is no relationship between variables with the sociodemography (age, gender, lastest education, and occupation). And respondent achievement level (TCR) showed that 80% were good at knowledge statements and 70% were good at attitude statements.